2015
DOI: 10.1097/md.0000000000001611
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapy for Primary Canaliculitis

Abstract: In patients with primary canaliculitis, conservative medical therapy is associated with a high recurrence rate. Surgical treatments carry a great resolution rate but sometimes can result in the lacrimal pump dysfunction and canalicular scarring. The aim of this study is to introduce a minimally invasive approach, intracanalicular ophthalmic corticosteroid/antibiotic combination ointment infiltration (IOI, intracanalicular ointment infiltration), and to report our preliminary results for treating primary canali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In most case reports, Actinomyces and Nocardia have been reported as the causative organisms of primary canaliculitis [5,79,15–17] ; however, recent reports have revealed that Staphylococcus and Streptococcus species are the most common causative organisms. [1,10,14,18] In the present case, the bacterial culture test could not identify the exact causative organism, but gram-positive rods were found. Additionally, the histologic examination identified tangled clumps of filamentous organisms, which are findings consistent with a diagnosis of sulfur granules.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In most case reports, Actinomyces and Nocardia have been reported as the causative organisms of primary canaliculitis [5,79,15–17] ; however, recent reports have revealed that Staphylococcus and Streptococcus species are the most common causative organisms. [1,10,14,18] In the present case, the bacterial culture test could not identify the exact causative organism, but gram-positive rods were found. Additionally, the histologic examination identified tangled clumps of filamentous organisms, which are findings consistent with a diagnosis of sulfur granules.…”
Section: Discussionmentioning
confidence: 52%
“…Some studies have reported that medical management is somewhat effective for treating primary canaliculitis, but the frequency of recurrence may be high due to the fact that such management cannot completely eradicate the bacterial reservoir. [5,79,13,18] In particular, it has been reported that medical treatment can have a recurrence rate of 33% [11] ; furthermore, there have been many other reports of failed cases using medical treatment. [2,6,7,13]…”
Section: Discussionmentioning
confidence: 99%
“…Canaliculitis appears at an average age of 60-65 years. 4,5 However, younger patients have also been reported. 6,7,8 When seen in infants and children, the clinician should be vigilant for other underlying lacrimal system pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that although surgery was more effective, canalicular irrigation could reduce the need for surgery. 5…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment contains oral and topical antibiotics with corticosteroid. [3,4] Due to the special anatomic structure of lacrimal duct, conservative therapy may lead to persistence or recurrence compared with surgery. [5,6] A high recurrence rate from 33-92% of conservative therapy has been found in the previous researches.…”
Section: Introductionmentioning
confidence: 99%